Setbacks in the road to self-injection: a descriptive study of provider and mystery client reports on the DMPA-SC care-seeking experience in Nigeria - Madeline Griffith; Sneha Challa; Ayobambo Jegede; Ivan Idiodi; Chioma Okoli; Aminat Tijani; Shakede Dimowo; Awawu Grace Nmadu; Elizabeth Omoluabi; Jenny Liu (Frontiers in Global Women's Health)
This mixed-methods study describes perspectives from health providers and simulated clients on initiation and continuation of DMPA-SC for self-injection in Nigeria. Through mystery (simulated) client interactions, we found that providers were similarly willing to dispense units of DMPA-SC for self-injection to different client profiles, which varied in age, marital status, and parity. However, in-depth interviews with providers revealed nuance in their approaches to assessing clients’ eligibility for unsupervised self-injection of DMPA-SC. Factors including client age, marital status, parity, and education influenced who they deemed able to self-inject, which may limit access to DMPA-SC for clients who wish to self-inject the method. Quantitative and qualitative data also indicated that clients faced setbacks in continuing unsupervised self-injection when seeking refills from an unfamiliar provider. Stockouts of DMPA-SC further complicated access; some providers resorted to purchasing DMPA-SC privately and passing the cost onto clients. These findings highlight the need for clearer refill protocols and more consistent supply to ensure equitable access to DMPA-SC for self-injection in Nigeria.